2021
DOI: 10.1039/d0cc07364d
|View full text |Cite
|
Sign up to set email alerts
|

Light-driven hydrogen production with CdSe quantum dots and a cobalt glutathione catalyst

Abstract: A robust photocatalytic system with CdSe QDs and a molecular cobalt catalyst produces H2 with high efficiency and activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Colloidal quantum dots (QDs) have attracted considerable interest in the optoelectronics and solar photochemistry communities because of their size-tunable electronic properties and high surface area-to-volume ratios. The ligand-nanocrystal boundaries of colloidal nanocrystals mediate the primary energy and charge transfer processes that give rise to photochemical or photocatalytic transformations at their surfaces. , Several examples of photochemical transformations involving energy and charge transfer processes have been reported including the use of QDs as redox photocatalysts where-in molecular species approach their surfaces and undergo photo-oxidation or reduction followed by subsequent radical–radical reactions. In other examples, redox shuttles such as viologens were used to extract photogenerated charges from colloidal nanocrystals for transport to cocatalysts also present in solution. Additionally, chemical transformations have been realized by design of the ligands as reagents in photochemical reactions, allowing the ligand-nanocrystal surface to function as a template for the final products. …”
Section: Introductionmentioning
confidence: 98%
“…Colloidal quantum dots (QDs) have attracted considerable interest in the optoelectronics and solar photochemistry communities because of their size-tunable electronic properties and high surface area-to-volume ratios. The ligand-nanocrystal boundaries of colloidal nanocrystals mediate the primary energy and charge transfer processes that give rise to photochemical or photocatalytic transformations at their surfaces. , Several examples of photochemical transformations involving energy and charge transfer processes have been reported including the use of QDs as redox photocatalysts where-in molecular species approach their surfaces and undergo photo-oxidation or reduction followed by subsequent radical–radical reactions. In other examples, redox shuttles such as viologens were used to extract photogenerated charges from colloidal nanocrystals for transport to cocatalysts also present in solution. Additionally, chemical transformations have been realized by design of the ligands as reagents in photochemical reactions, allowing the ligand-nanocrystal surface to function as a template for the final products. …”
Section: Introductionmentioning
confidence: 98%
“…Colloidal semiconductor nanocrystals are actively being studied as photocatalysts for fuel production and environmental remediation. The small dimensions of nanocrystals efficiently suppress the bulk recombination of photoexcited charge carriers due to the short diffusion distances required to reach the surface. , However, the fate of photoexcited charges once they reach the surface, that is, whether they recombine or are extracted to initiate useful redox reactions, is highly sensitive to the structure of the surface. Organic ligands that bind to atoms on the nanocrystal surface are commonly used to control the size and shape of colloidal metal and semiconductor nanocrystals. , Residual ligands that block access to the particle surface can poison the nanocatalyst. , However, recent studies have shown that organic ligands can tune the activity and selectivity of nanocatalysts by regulating competitive adsorption of substrate molecules and inhibitors to surface sites, changing the electronic structure at the surface, and/or acting as redox shuttles to facilitate interfacial charge transfer. , Although controlling surface–ligand interactions is critical in the design of nanocatalysts, conventional measurements of catalytic activity only provide ensemble-averaged structure–activity trends.…”
mentioning
confidence: 99%
“…Developing catalysts capable of "selfhealing" has been another goal in catalysis for energy, given the need for such catalysts to maintain high activity on a large scale for long periods of time in any practical application [71,72]. A step in this direction was shown recently by the ability of an H 2 evolution catalyst to self-assemble in situ, yielding a longlasting system for light-driven H 2 evolution [73].…”
Section: Intermolecular Proton Deliverymentioning
confidence: 99%
“…Nature again provides inspiration through its mechanisms of repair [82,83]. The in situ generation of the cobalt-glutathione catalyst discussed above [73] is one example of a self-assembling, self-repairing catalyst for hydrogen production, but the relationship of structure and dynamics of that system to activity remains poorly understood. Further efforts are needed to yield catalytic systems that are efficient and robust and also can be investigated in detail.…”
Section: Proton Reduction: Progress and Prospectsmentioning
confidence: 99%